2022
DOI: 10.3390/separations9080190
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Alpha-Glucosidase and Alpha-Amylase Inhibitory Activities and Antioxidant Capacity of Helichrysum cymosum and Helichrysum pandurifolium Schrank Constituents

Abstract: Diabetes mellitus (DM) is a group of systemic metabolic disorders with a high rate of morbidity and mortality worldwide. Due to the detrimental side effects of the current treatment, there is a great need to develop more effective antidiabetic drugs with fewer side effects. Natural products are a well-known source for the discovery of new scaffolds for drug discovery, including new antidiabetic drugs. The genus Helichrysum has been shown to produce antidiabetic natural products. In this investigation, the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Similarly, along with their powerful antioxidant action, phenolic-rich samples have been shown to have a high potential for suppressing the activity of the α-glucosidase enzyme [ 124 ]. In addition, several studies have demonstrated that phytochemicals from plants and algae might be a rich natural supply of phenolic and flavonoid compounds, which are well-known for their significant hypoglycemic potential [ 126 , 127 ]. It is important to point out that the ethanolic extract obtained from Leptolyngbya sp.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, along with their powerful antioxidant action, phenolic-rich samples have been shown to have a high potential for suppressing the activity of the α-glucosidase enzyme [ 124 ]. In addition, several studies have demonstrated that phytochemicals from plants and algae might be a rich natural supply of phenolic and flavonoid compounds, which are well-known for their significant hypoglycemic potential [ 126 , 127 ]. It is important to point out that the ethanolic extract obtained from Leptolyngbya sp.…”
Section: Resultsmentioning
confidence: 99%
“…Enzyme inhibition is, therefore, the basis of many drugs. The results for the inhibition of various enzymes indicate the effects of G. pictum on metabolic diseases, such as diabetes, and neurodegenerative diseases, such as AD, which are usually accompanied by oxidative stress [ 5 , 58 ]. In enzyme inhibitory assays, notably diabetic enzymes, the presence of a five-membered furan moiety in the furanolabdane diterpenoids Hypopurin E, Hypopurin B and Hypopurin A contributes to the inhibitory activity of the enzymes [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts to curb the prevalence of diabetes mellitus, the disease is still on the rise. Hence, an effective therapeutic approach targeting diabetes precursor enzymes such as α-amylase and α‐glucosidase for treating diabetes will be of significant benefit [ 8 , 9 ]. The α-amylase enzyme converts oligosaccharides to polysaccharides [ 10 ], while α-glucosidase catalyzes the final phase of carbohydrate hydrolysis, resulting in absorbable monosaccharides [ 11 ].…”
Section: Introductionmentioning
confidence: 99%